Pengaruh Produk, Harga, Promosi, Tempat, Orang, Proses, Bukti Fisik Terhadap Keputusan Konsumen Membeli Jasa Kamar Superior Pada Hotel Santika Pontianak - Samsuddin S; Hari Suseno (JURNAL MANAJEMEN MOTIVASI, 2014)
This study aims to determine the effect of marketing mix consisting of product, price, promotion, place, people, process, physical evidence against the decision of consumers to buy services superior rooms at Hotel Santika Pontianak. Descriptive method used in this study, with data obtained through observation, interviews, and questionnaires to all consumers who ever bought a superior room service at Hotel Santika Pontianak. Sample of 100 people were selected using purposive sampling technique taken from consumers who ever bought a superior room service. Variables used in this research consisted of independent variables and the dependent variable, independent variable used consists of the product (X1), price (X2), promotion (X3), where (X4), people (X5), process (X6), and evidence physical (X7). The analysis technique used is quantitative analysis of regression. The results of this study indicate that the marketing mix consisting of product, price, promotion, place, people, process, physical evidence simultaneously significantly influence the consumer's decision to buy services of superior rooms at Hotel Santika Pontianak, whereas only a partial and processes influence the consumer's decision to buy services. Factor of product, price, promotion, place, people, process, physical evidence influence the consumer's decision to buy services of superior rooms at Hotel Santika Pontianak by 44.3% while the remaining 55.7% is influenced by other factors outside of this research